Blockchain-based data governance for privacy-preserving in multi-stakeholder settings - Garcia, Rodrigo Dutra; Ueyama, Jó (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2024: Anais Estendidos do XXIV Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2024)
In multi-stakeholder systems such as healthcare, the Internet of Things, and supply chain management, data is often generated and shared. As a result, data owners aim to maintain control and privacy over their data, while data consumers need reliable methods to verify the data’s origins and creators. These conflicting interests require data governance systems to ensure data provenance, privacy protection, consent management, and selective disclosure. To address these challenges, this research proposed a decentralized data governance system that utilizes blockchain technology, proxy re-encryption (PRE), and Boneh, Boyen, and Shacham (BBS) signatures. The proposed system enables data owners to control, selectively share, and track their data through privacy protection, consent management, and selective disclosure mechanisms. It also allows data consumers to understand the data’s lineage through a blockchain-based provenance mechanism. The research focused on analyzing electronic prescription use cases that contain sensitive data and involve multiple stakeholders, such as patients, doctors, and pharmacists. The research was structured as a collection of published articles organized in the following sequence: problem formulation and developing smart contracts, implementing privacy and consent management through PRE, and applying BBS signatures for selective data sharing. The proof-of-concept implementation and evaluations were conducted using CosmWasm, Hyperledger Besu, Ethereum, pyUmbral PRE, and BBS signatures. The evaluations show that the proposed decentralized system is platform-agnostic, scalable, and capable of providing higher transparency, privacy, and trust, all with minimal overhead.